PENGARUH KREDIT MACET TERHADAP KINERJA KEUANGAN PADA KSP KOPDIT HIRO HELING CABANG MAUMERE TAHUN 2020-2024 - Imelda Atnasia Lambertini; Emilianus Eo Kutu Goo; Elisabet Luju (Universitas Nusa Nipa Maumere, 2026)
This study aims to examine the influence of non-performing loans (NPLs) on the financial performance of KSP Kopdit Hiro Heling, Maumere Branch, during the period 2020–2024. Non-performing loans are among the most critical issues faced by credit unions, as they can disrupt liquidity, reduce income, and negatively affect the distribution of the Remaining Operating Results (SHU). The research adopts a descriptive method with a qualitative approach. Data sources include both primary and secondary data. Primary data were collected through direct interviews with the General Manager and Manager of KSP Kopdit Hiro Heling, Maumere Branch, while secondary data consist of loan disbursement records and NPL statistics covering the 2020–2024 period. The findings reveal that the level of non-performing loans fluctuated throughout the study period, directly impacting the cooperative’s financial performance. These fluctuations affected liquidity and SHU, which also varied annually. An increase in NPLs led to a decline in SHU due to reduced interest income and rising uncollectible receivables, whereas a decrease in NPLs contributed to improved SHU and enhanced financial stability. Interviews further indicated that NPLs were influenced by members’ limited repayment capacity, misuse of loans, weak monitoring, and external factors such as the COVID-19 pandemic and members’ economic conditions. The study concludes that higher levels of NPLs increase the risk of declining financial performance and SHU. Therefore, KSP Kopdit Hiro Heling, Maumere Branch, must strengthen creditworthiness analysis, improve monitoring and member assistance, and enhance collection systems to mitigate NPLs and safeguard financial stability in the future.